Roles of Brain Angiotensin II in Cognitive Function and Dementia - Masaki Mogi; Jun Iwanami; Masatsugu Horiuchi (International Journal of Hypertension)
The brain renin-angiotensin system (RAS) has been highlighted as having a pathological role in stroke, dementia, and neurodegenerative disease. Particularly, in dementia, epidemiological studies indicate a preventive effect of RAS blockade on cognitive impairment in Alzheimer disease (AD). Moreover, basic experiments suggest a role of brain angiotensin II in neural injury, neuroinflammation, and cognitive function and that RAS blockade attenuates cognitive impairment in rodent dementia models of AD. Therefore, RAS regulation is expected to have therapeutic potential for AD. Here, we discuss the role of angiotensin II in cognitive impairment and AD. Angiotensin II binds to the type 2 receptor (AT2) and works mainly by binding with the type 1 receptor (AT1). AT2 receptor signaling plays a role in protection against multiple-organ damage. A direct AT2 receptor agonist is now available and is expected to reduce inflammation and oxidative stress and enhance cell differentiation. We and other groups reported that AT2 receptor activation enhances neuronal differentiation and neurite outgrowth in the brain. Here, we also review the effect of the AT2 receptor on cognitive function. RAS modulation may be a new therapeutic option for dementia including AD in the future.